Uterine adenocarcinoma in Quarter Horse mare. (23rd August 2017) - Lopez, C.; Ciccarelli, M.; Gold, J. R.; Tibary, A.
Summary: Uterine adenocarcinoma was diagnosed in a 16‐year‐old Quarter Horse mare that presented for fever, stranguria, anorexia and a history of weight loss. A mass at the level of the cervix and uterine body was identified by transrectal palpation. Biopsy of the cervix revealed an antemortem diagnosis of adenocarcinoma. Thoracic ultrasonography revealed multiple areas of consolidation in the lung, and comet tail artefact along the entire pleural surface. Post‐mortem examination confirmed the endometrial adenocarcinoma with metastasis to urinary bladder, ureters, lungs, tracheobronchial lymph nodes and bone marrow.